Humor Has It - Fluxus: Purge - Promote - Fuse (Nam June Paik Art Center, 2021)
Artists: Nam June Paik, Erik Andersch, Ay-O, Klaus Barisch, Joseph Beuys, George Brecht, John Cage, Willem de Ridder, Robert Filliou, Geoffrey Hendricks, Dick Higgins, Takehisa Kosugi, Manfred Leve, George Maciunas, Jonas Mekas, Manfred Montwe, Peter Moore, Charlotte Moorman, Yoko Ono, Benjamin Patterson, Mieko (Chieko) Shiomi, Karlheinz Stockhausen, Daniel Spoerri, Ben Vautier, Wolf Vostell, Robert Watts, Emmett Williams, Jud Yalkut, La Monte Young. Texts: Kim Seong Eun, Park Sang Ae, Woo Jung-Ah, Hyejin Park, Jung Yunhoe, Yook Youngshin
English Arabic
Keywords: N4390-5098 Visual Arts. Exhibitions